Cooperation between the EU, NATO and the UN in addressing global security challenges: a critical analysis - Sergiy Lukin; Yevhenii Taran; Oleksander Tykhonenko (Clío, 2025)
The aim of the study is to analyse the cooperation of international organizations in shaping a global security strategy and countering modern threats. The research employed the following methods: graphical comparison, statistical and comparative analysis, and case study. The role of strategic documents and the role of international organizations in ensuring the security of member states is determined. The differences in resources between countries are identified, which emphasize the need for targeted capacity-building initiatives. Strategies for countering hybrid threats that combine conventional and unconventional tactics are investigated on the basis of 11 selected countries. The conclusion is made about the key role of international organizations in countering global security threats and the main focus of the UN, NATO and EU in performing their own functions to ensure stability. Further efforts should focus on adaptive strategies and coherent policies to address the interconnected current security challenges